(untitled) (Journal of Imam Al-Kadhim College, 2023)
In the name of God, the Most Gracious, the Most Merciful, and praise be to God, Lord of the worlds, and prayers and peace be upon the best of creation and the seal of the messengers the honorable Prophet Muhammad, may God’s prayers and peace be upon him and his family, and after... We will discuss the hadith and the study of a number of Qur’anic stories that were mentioned in the Bible, which Christians adopt as a heavenly book that God Almighty sent down to guide them in their rulings, legislation, and laws of their lives. It is known that there are only four Gospels that were approved by the official church in the late second century AD. These gospels are due to the fact that Christ (PBUH) did not leave a written trace, but rather oral teachings and a biography of his life. In fact, the Gospels that we know today were not the first written effect that the early Christians used to work with, as they were preceded by the letters of Paul the Apostle that appeared successively between the year 51 and the year 67 AD. It was the year in which he was martyred in the city of Rome during the widespread wave of persecution against Christians in the days of Emperor Nero, but Paul’s letters themselves did not contain anything regarding the life of Christ or his deeds, sayings and miracles. And Paul’s teachings begin with the risen Christ, Lord and Savior, and end with Him. He did not refer with a single word to the Virgin Mary (PBUH), nor to the miraculous birth of Christ, nor to the events that led to his trial and crucifixion, and this means that forty years Or the like has passed since the death of Christ without the church having an approved document regarding him, but rather a group of messages of a theological nature whose main subject is not focused on the life of Christ, but rather on the salvific effects of his crucifixion, death and resurrection. And when most of the members of the generation who heard about Jesus directly or heard from the disciples of Christ died, bringing with them their memories and direct impressions, the differences and contradictions within the early Church surfaced, and there was an urgent need to write down the life and teachings of Jesus, with the aim of confirming the Christian belief on the one hand, or affirming This or that group’s point of view. Thus, the four Gospels appeared in succession, which were attributed either to personalities from the era of the prophecy of Christ, such as Mark and Luke, or to his direct disciples, such as Matthew and John. All of these Gospels were written in the Greek language, which was the language of culture in that era. Matthew, the Gospel of Mark, the Gospel of Luke and the Gospel of John), in addition to these Gospels, the Christian Bible contains a number of books, namely: the letters of Paul the Apostle, the letters of James, two letters to Peter, three letters to John, the letter of Judas and the Acts of the Apostles attributed to Luke, in addition to These books were considered canonical and written under the inspiration of the Holy Spirit. There are a number of Gospels that were not sanctioned by the official Church, and falsely considered them to the names of prominent figures in the New Testament, such as the Gospel of Jacob, the Gospel of Jacob, the Gospel of Matthew, the Arab Bible, and the Israeli Gospel of Thomas. And the history of Youssef Al-Najjar. Most of these gospels are concerned with the history of Mary’s family, her childhood and her previous life, the birth and childhood of Christ, and other topics that did not receive much attention from the authors of the official gospels. Although these gospels remained on the sidelines of the official books of the New Testament, they were widely circulated and played an important role in providing rich material to the popular imagination and Christian piety. Modern, such as the birth of the Virgin, her presentation to the Temple, the nativity cave, and the angel’s annunciation to Mary as she sits weaving the veil of the Temple. It also provided rich material for music and church hymns, and some of its events became festive religious occasions, such as the feast of the Ascension of the Virgin Mary. At the beginning of the seventh century AD, at the advent of Islam, the Christian world was drowning in the apocryphal Gospels, and the central church had not completely succeeded in standardizing the Christian belief and eliminating what it called heresies that carried ideas and visions that were inconsistent with the decisions of the successive ecumenical councils since the Council of Nicaea in the year 325 m. This means that the Qur’an was revealed in a cultural climate fraught with controversy between Christians and Jews on the one hand, between Christianity and paganism on the other, and between rival Christian sects on the third. Among the stories and stories mentioned in the Gospels, especially those that represent the New Testament recognized by the Church. Here, in this research, we will return to these Gospels approved by the Church, and trace some points of convergence with the similar stories mentioned in the Holy Qur’an, because the Qur’anic narrative contains rich material similar to that of the Gospels, and the aim behind that is to show the similarity between the Biblical narrative and the novel Quranic; Which makes the Qur’anic novel more like a novel based on an internal Christian controversy, not on a controversy between two different religions, and we will also, through the folds of the research, make a comparison between Christian theology, which was woven slowly and over several centuries by the decisions of the Ecumenical Councils, and the theology of the Holy Qur’an as reflected in its controversy with People of the book. Is there any similarity or difference between the Holy Qur’an, which is a guidance for all people, including other religions, and the Bible, which is the law of the Christian religion? This is what we will study in our research by presenting an introduction and one chapter with two chapters and a conclusion, provided that the methodology is complete and the information is correct presented in an understandable and sound manner, with an illustration of a set of examples and evidence taken from the Holy Qur’an and the Bible that tells the subject of fasting in both the Qur’an and the Holy Qur’an.